Motivasi Anggota Komunitas Lari di Kota Semarang - Adi, Wahyu Fitri; Candra, Adiska Rani Ditya (Indonesian Journal of Physical Education and Sport Science, 2024)
Studi purpose. This study aims to determine the level of motivation among running community members in Semarang City regarding the sport of running. Materials and methods. This study uses a research method employing a survey approach. The subjects in the study are members of a running community in Semarang City, totaling 50 people. Consisting of 40 men and 10 women. The research instrument uses a motivation questionnaire that has been tested for validity with a value of 0.36 - 0.75 and a reliability value of 0.946. The data analysis technique uses quantitative descriptive analysis by finding the mean, standard of deviation, minimum and maximum value, data analysis using Microsoft Excel and SPSS 25 version. Results. Based on the results of the research on the motivation of running community members in Semarang show that their motivation level reaches 60%, which falls into the very high motivation category. In terms of intrinsic motivation, 50% of the running community members in Semarang are influenced by enjoyment aspect, with a percentage value of 35% and the fitness aspect 35%, both categorized as very high. Meanwhile, extrinsic motivation has a percentage value of 45%, driven by social interaction with 53% of the running community members in Semarang falling into the very high motivation category. Conclusions. Based on the research findings, the motivation level of running community members in Semarang City to engage in running is classified as very high, influenced by intrinsic motivations such as enjoyment and fitness, as well as extrinsic motivations like social interaction.